Sapta Cipta Rasa Tunggal Offering Dance at the 51st Dies Natalis of ISI Surakarta - Suharji suharji; Soemaryatmi Soemaryatmi; Darmasti Darmasti; Efrida Efrida; Sumargono Sumargono; Sri Ningsih Sukirman (Institut Seni Indonesia Surakarta, 2022)
This research is a case study of the performance of the offering dance at the ISI Surakarta 51st Dies Natalis Ceremony (held on July 15th, 2015) by seven dancers. The seven dancers previously acted as leaders of the Senate procession, after the members of the senate sat in their seats, they danced to express the character of Bima so that it could be said that the dance was part of the ceremonial event. The sesaji dance is an expression of Bima's character, which in Javanese collective knowledge is a complex system of symbols. This phenomenon is approached through the constructivism paradigm, especially from the point of view of interpretivism where the methodological mission is to elaborate a reflective events. The research question posed is what constitutes a gift or alms in the Sapta Cipta Rasa Tunggal – title of that dance — as offering dance considering that offerings lexico-etymologically means giving alms or charity. Triangulative data as objects of observation are videos of dance performances via the YouTube platform, interviews with source persons, and library data. The conclusions drawn are: 1) this sesaji dance is a form of mnemonic (kinetic mnemonic) in the form of motion as a tool for reflective memory; 2) offering dance and imitation of the imaginary character in the kind of the Bima containing doxa – knowledge that does not need to be verified – that the ethical attitudes that humans should have are teteg, tatag, teguh, tanggon, and tanggap.